2019
DOI: 10.1089/neu.2018.5824
|View full text |Cite
|
Sign up to set email alerts
|

Retracted: Inhaled Nitric Oxide Protects Cerebral Autoregulation and Reduces Hippocampal Neuronal Cell Necrosis after Traumatic Brain Injury in Newborn and Juvenile Pigs

Abstract: Traumatic brain injury (TBI) contributes to morbidity in children, and boys are disproportionately represented. Cerebral blood flow (CBF) is reduced and autoregulation is impaired after TBI, contributing to poor outcome. Cerebral perfusion pressure (CPP) is often normalized by use of vasoactive agents to increase mean arterial pressure (MAP). In prior studies of male and female newborn and juvenile pigs, we observed that phenylephrine, norepinephrine, epinephrine, and dopamine demonstrated different sex- and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Somewhat surprisingly, though, statistically significant pial artery dilation, which reflects an increase in CBF, and an increase in calculated CPP were not consistently observed with iNO (Hekierski et al 2018). Nonetheless, it was observed that reductions in blood flow in the hippocampus associated with FPI were blocked by iNO (Hekierski et al 2018), supportive of the neurovascular unit concept and neuroprotection via improved CBF. Importantly, iNO did not produce a confounding drop in MAP.…”
Section: Inhaled Nitric Oxide Improves Outcome In Preclinical Experimmentioning
confidence: 91%
See 1 more Smart Citation
“…Somewhat surprisingly, though, statistically significant pial artery dilation, which reflects an increase in CBF, and an increase in calculated CPP were not consistently observed with iNO (Hekierski et al 2018). Nonetheless, it was observed that reductions in blood flow in the hippocampus associated with FPI were blocked by iNO (Hekierski et al 2018), supportive of the neurovascular unit concept and neuroprotection via improved CBF. Importantly, iNO did not produce a confounding drop in MAP.…”
Section: Inhaled Nitric Oxide Improves Outcome In Preclinical Experimmentioning
confidence: 91%
“…An alternative strategy to normalize CPP could involve administration of a cerebrovasodilator to elevate CBF. Recently, it was observed that inhaled NO (iNO) prevented impairment of cerebral autoregulation and neuronal cell necrosis in hippocampal regions CA1 and CA3 after FPI in both male and female newborn and juvenile pigs (Hekierski et al 2018). The fact that outcome was improved regardless of sex and age is significant clinically since the above discussion centered on the need for use of a single vasoactive agent to elevate MAP and normalize CPP in treatment of pediatric TBI.…”
Section: Inhaled Nitric Oxide Improves Outcome In Preclinical Experimmentioning
confidence: 99%
“…Only one other medication has recently been observed to improve outcome in both newborn males and females after TBI, and that is inhaled nitric oxide. 13 The results of the present study show that there is at least one additional medication that can achieve protection in a sex-independent manner.…”
Section: Discussionmentioning
confidence: 49%
“…One study found that when nitric oxide was administered post-TBI via inhalation in mice, there was a significantly reduced lesion volume and brain edema with less disruption to the blood-brain barrier and improved neurological function [61]. Similarly, another group reported that nitric oxide administration significantly protected against TBI-induced neuronal cell necrosis and maintained cerebral autoregulation of blood flow in juvenile pigs [62].…”
Section: Role Of Nitric Oxide In Tbis and Concussionsmentioning
confidence: 99%